Graciliano: ramos excluídos - Carvalho, Antonio Morais de (2005)
This work aims at calling the attention to the reading of Insônia, by Graciliano Ramos, a collection of short stories which has been neglected by most literary critics, under the allegation that it is an inferior book to the others by the same author, having texts produced under circumstantial force, without the same accuracy of the other books. In a first moment, we present a critical revision of the critical reception of Insônia; in a second, we develop a reading of each short story. Although we know of the provisory character of this reading, we hope it may partially reveal the same accuracy of composition, the same effort at expression, the same world vision characteristic of the other books.